Am I Going to Heaven? First Step Climbing the Stairway to Heaven Model Results from a Case Study in Industry - Santos, Paulo Sérgio dos; Barcellos, Monalessa P.; Calhau, Rodrigo Fernandes (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Context: Nowadays, software development organizations have adopted agile practices and data-driven software development aiming at competitive advantage. Moving from traditional to agile and data-driven software development requires changes in the organization culture and structure, which may not be easy. Stairway to Heaven Model (StH) describes this evolution path in five stages. Objective: We aimed to investigate how Systems Theory tools, GUT Matrix and reference ontologies can help organizations in the first transition of StH, i.e., moving from traditional to agile development. Method: We performed a participative case study in a Brazilian organization that develops software in partnership with a European organization. We applied Systems Theory tools (systemic maps and archetypes) to understand the organization and identify undesirable behaviors and their causes, and also GUT matrices to decide about which ones should be addressed first; we defined strategies to change the undesirable behaviors by implementing agile practices, and we used reference ontologies to share a common understanding about agile concepts. Results: By understanding the organization, a decision was made to implement a combination of agile and traditional practices. The implemented strategies improved software quality and project time and cost. Problems due to misunderstanding agile concepts were solved, allowing the organization to experience agile culture and foresee changes in its business model. Conclusion: Systems Theory tools and GUT Matrix aid organizations to move from traditional to agile development by supporting better understand the organization, find leverage points of change and enabling to define strategies aligned to the organization characteristics and priorities. Reference ontologies can be useful to establish a common understanding about agile, enabling teams to be aware of and, thus, more committed to agile practices and concepts.